2018
DOI: 10.1002/dmrr.3054
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome and the risk of cardiometabolic complications in longitudinal studies

Abstract: The purpose of this study was to perform a review of the longitudinal studies to determine whether polycystic ovary syndrome is associated with higher prevalence of metabolic complications and cardiovascular morbidity and mortality. The primary outcomes included body mass index, metabolic syndrome and its components (waist circumference, lipid profile, arterial hypertension, abnormal glucose metabolism (impaired fasting glucose, impaired glucose tolerance, type 2 diabetes), insulin resistance, and cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 174 publications
(564 reference statements)
0
20
1
1
Order By: Relevance
“…It has also been observed that fat distribution is altered in PCOS patients and that this group presents greater tendency to increased VAT accumulation in comparison to the general population [17]. Moreover, it has been shown that VAT is associated with insulin resistance and increased metabolic risk in PCOS women [21], and that increased concentrations of androgens are connected with abdominal fat deposition [22]. Therefore, our results confirmed that phenotype A could be considered a phenotype with increased risk of obesity, type 2 diabetes, coronary heart disease and other metabolic disorders [23], and it may be related to significantly higher FAI in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that fat distribution is altered in PCOS patients and that this group presents greater tendency to increased VAT accumulation in comparison to the general population [17]. Moreover, it has been shown that VAT is associated with insulin resistance and increased metabolic risk in PCOS women [21], and that increased concentrations of androgens are connected with abdominal fat deposition [22]. Therefore, our results confirmed that phenotype A could be considered a phenotype with increased risk of obesity, type 2 diabetes, coronary heart disease and other metabolic disorders [23], and it may be related to significantly higher FAI in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Women with PCOS are also at an increased risk for the development of both T2DM and CVD risk factors with their higher rates of overweight/obesity including central obesity and dyslipidemia. Although predicted, a higher risk for CVD mortality has not so far been reported due to the paucity of population-based long-term studies [66,67].…”
Section: Women With Gestational Diabetes: a Special Female Populationmentioning
confidence: 99%
“…Consequently, the prevalence of metabolic syndrome (MetS) is found to be at least threefold higher in women with PCOS compared to general population [ 32 ] and is estimated at 33% to 47% [ 18 , 33 ]. Interestingly, although PCOS patients have a proven increased prevalence of cardiovascular disease risk factors, the risk of cardiovascular morbidity and mortality is still equivocal [ 34 , 35 ]. To explain this phenomenon, longitudinal studies with PCOS women should be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Although a lot of reports concerning metabolic consequences in PCOS have been published, almost all of them were designed as cross-sectional studies. There is a paucity of studies with long-term follow-up in which the detailed metabolic profile in women with PCOS was re-evaluated [ 35 ] and therefore, the course and development of metabolic disorders as well as the factors which impact on the subsequent complications in women with PCOS are poorly explored. The main aim of the present study was to determine the impact of ageing on glucose metabolism, insulin sensitivity, anthropometric parameters, lipid profile and values of blood pressure (BP) in a cohort of 31 women with previously diagnosed PCOS according to the Rotterdam criteria.…”
Section: Introductionmentioning
confidence: 99%